الروايات الواردة في وجود الإمام الثاني عشر وغيبته : دراسة مقارنة بين السنة والشيعة الإمامية - أوكتان، يوسف (Kulliyah of Islamic Revealed Knowledge and Human Sciences,al-Jami'at al-Islamiyyah al- 'Alamiyyah Maliziya, 2019)
This research compares between the prophetic traditions narrated by the Sunni about the presence and absence of the twelfth Imam and those related by the Imamate Shia. It explains the concept of Imamate and Mahdi as understood and conceived by the two sects. In addition, it accounts for the chronicles presented by some Sunni scholars as evidence to the birth and absence of the twelfth Imam, which are equally used by the Imamate Shia as counter-argument against the former. The research also shows that there is no implicit relationship in the concept of Mahdi between the Sunni and the Shia. The research uses inductive approach to trace the prophetic traditions as well as some statements made by scholars about the absence and presence of the twelfth Imam. In addition, it uses analytical approach to analyze the prophetic traditions pertaining to the twelfth Imam with special focus on the main texts. It uses comparative approach as well. The research has concluded some findings: the most important of which that the Imamate Shia have appropriated and used the prophetic traditions related by the Sunni about the rise of Mahdi at the end time in order to prove the credibility of their belief with the claim that no one has ever understood the aforementioned narrations as have the Imamate Shia. Likewise, they have provided as evidence the statements made by Sunni scholars to prove the birth and disappearance of Mahdi—all these to demonstrate the authenticity of their creed. Hence, these scholars are either historians who accounted for what is a common knowledge, and therefore, related historical accounts that are already known, or they are considered not to be amongst the Sunni scholars, or those Sunni scholars who made the mention of the birth and absence of the twelfth Imam in their writings, did so, by chiefly depending on accounts related by the Imamate Shia. They did so, not because they conceded the belief of Shia in this regard, but it was rather an attempt by the Sunni scholars to highlight and explain the Shi'i school of thought. It also may have been possible that those scholars became Shiite—a fact that was a common knowledge within the Sunni school of thought. It may possibly have been true that those scholars, whose writings were replete with narrations and statements related to the twelfth Imam, were actually appropriated and inserted by the Shia. The research shows that there are differences and contradictions in the chronicles by the Shia about the birth and absence of the twelfth Imam, let alone that these chronicles are flawed and untenable.